Optimization of irrigation and nitrogen for sustainable rice cultivation: emissions and yield impact - Ashwini, S; Sakthivel, N; Pazhanivelan, S; Ramah, K; Janaki, P; Ravichandran, V (Plant Science Today, 2025)
Rice cultivation is integral to global food security and exports but contributes significantly to greenhouse gas emissions, mainly methane (CH?) and nitrous oxide (N?O), exacerbating climate change. This study evaluates the effects of three irrigation practices-conventional flooding (CF), alternate wetting and drying (AWD) and the modified system of rice intensification (MSRI) on CH? and N?O emissions and rice yields over two seasons (Kar 2022 and Samba 2023). A split-plot design with five nitrogen management strategies was employed, with weekly gas sampling and yield measurements at harvest. Among the treatments, the MSRI method, combined with 75% of the recommended nitrogen dose and a 0.4% foliar nano-urea spray (M3S5), recorded the lowest CH? emissions at 50-60 mg CH?/m²/day, compared to 120-130 mg CH?/m²/day under CF. In contrast, N?O emissions under MSRI peaked at 11-13 µg N?O/m²/day, higher than CF (5-7 µg N?O/m²/day). MSRI also achieved the highest rice yields, averaging 6029 kg/ha in Kar 2022 and 6018 kg/ha in Samba 2023, compared to 5500-5700 kg/ha under AWD. These findings highlight the potential of MSRI with optimized nitrogen management as a sustainable alternative, balancing high productivity with reduced CH? emissions and offering a pathway for climate-resilient rice farming.